COMPUTER VISION SYNDROME AND TENSION TYPE HEADACHE IN COMPUTER WORKERS - Hamdani, Delincia; Kurniawati, Nita; Ernawati, Titiek (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2021)
Introduction: Nowadays, the average human uses digital tools for their daily needs such aswork, study, and communication. One of the most commonly used is a computer. Long-termuse of computers can cause several complex problems in the eyes and vision, such as eyefatigue, eye irritation, red eyes, blurred vision, dry eyes, neck and shoulder pain, andheadache that can be referred to as Computer Vision Syndrome. Tension-Type headache(TTH) is a headache with a binding sensation with mild to a moderate intensity that lasts forseveral minutes to days, that might be caused by excessive contraction of muscle due tofatigue at work. Therefore, there is a possibility that there is an association between ComputerVision Syndrome and Tension-Type Headache. Purpose: To analyze the association between CVS and TTH in Computer Workers. Method: Cross-sectional design was used in this research, and the sampling method wasconsecutive sampling, and a questionnaire was used. The research period was two days, from16th to 17th July 2019, at Graha Pena Building, Surabaya. Results: Respondent that experienced CVS was 61,9%, TTH was 27,6%, both CVS and TTHwas 19,4%, and analysis with chi-square test, showed p=0,220 which means that there’s noassociation between CVS and TTH. Conclusion: There’s no association between CVS and TTH in Computer Workers.